2021
DOI: 10.1111/ejn.15181
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet during adulthood interacts with prenatal stress, affecting both brain inflammatory and neuroendocrine markers in male rats

Abstract: Prenatal stress (PNS) affects foetal programming and, through an interaction with subsequent challenges, can increase vulnerability to mood and metabolic disorders. We have previously shown that, following PNS, adult male rats are characterized by increased vulnerability to a metabolic stressor experienced at adulthood (8‐week‐high‐fat diet—HFD). In this study, we specifically assessed whether PNS might interact with an adult metabolic challenge to induce an inflammatory phenotype. Changes in the expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Excessive BMI before and during pregnancy has been associated with insulin resistance and gestational diabetes and is more likely to result in life-threatening conditions (both for the mother and the offspring) such as pre-eclampsia [ 91 ]. Moreover, it has been related to perinatal morbidity and to an overall increased chance for the offspring to develop metabolic, cardiovascular, and mental health disorders throughout life [ 8 , 14 , 92 ]. To this regard, an interesting meta-analysis performed by Thangaratinam and co-workers suggests that dietary interventions are the most effective way to contrast maternal obesity.…”
Section: Nutritional Strategies To Counteract Maternal Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive BMI before and during pregnancy has been associated with insulin resistance and gestational diabetes and is more likely to result in life-threatening conditions (both for the mother and the offspring) such as pre-eclampsia [ 91 ]. Moreover, it has been related to perinatal morbidity and to an overall increased chance for the offspring to develop metabolic, cardiovascular, and mental health disorders throughout life [ 8 , 14 , 92 ]. To this regard, an interesting meta-analysis performed by Thangaratinam and co-workers suggests that dietary interventions are the most effective way to contrast maternal obesity.…”
Section: Nutritional Strategies To Counteract Maternal Obesitymentioning
confidence: 99%
“…OS and inflammation are main features of obesity and play a pivotal role in mediating the negative effects of this condition during pregnancy for both the mother and the offspring [ 8 , 92 , 161 ]. Indeed, a tight regulation of the redox balance and inflammatory processes, particularly during pregnancy, is crucial for a proper fetal development [ 14 , 162 ]. Moreover, OS has been reported to impair human placental amino acid uptake and increase Na+ permeability, directly affecting amino acid transporters [ 163 ].…”
Section: Nutritional Strategies To Counteract Maternal Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Obese mice experienced a decline in cognitive function after a long-term high-fat diet, accompanied by corresponding pathological changes in hippocampal neurons, which are closely related to the decline of BDNF levels in hippocampus. Recent studies have found that obesity can induce hippocampal inflammation and impairs emotion related to the hippocampus (21).…”
Section: Introductionmentioning
confidence: 99%
“…One is certainly the timing of the stressful challenge and the context. Especially early in life exposure to adversity has lasting impacts on brain and behaviour (Čater & Majdič, 2021; Clinton et al, 2021; Roque et al, 2021; Wang et al, 2021), specifically also with regard to addiction and reward circuitry (Roque et al, 2021; Rudolph et al, 2020; Levis et al, 2021; Mooney‐Leber et al, 2021), pain responding (Melchior et al, 2021), epigenetic programming (Alyamani et al, 2021; Womersley et al, 2021), neuroinflammation (Friend et al, 2020; Marsland et al, 2021) and in interaction with the metabolic regulation (Berry et al, 2021). Beyond this, it is even unclear how ‘normative’ developmental experiences contribute to stress‐related behaviours (Farber et al, 2020), but it may be that broader environmental factors, such as access to green space, may contribute to resilience and reduced stress responding (Rojas‐Carvajal et al, 2021).…”
mentioning
confidence: 99%